The Effectiveness Of Criminal Law In Combating Sexual Violence Against Children After The Enactment Of Law Number 12 Of 2022 On Sexual Violence Crimes - Muhammad Ridho Firmansyah; Dwi Putra Jaya; Ferawati Royani (Jurnal Multidisiplin, 2026)
Sexual violence against children is a serious crime that causes long-term physical, psychological, and social impacts on victims. The enactment of Law Number 12 of 2022 on Sexual Violence Crimes (UU TPKS) represents a progressive step in strengthening legal protection for victims, particularly children as a vulnerable group. This research aims to analyze the effectiveness of criminal law in combating sexual violence against children following the enactment of the UU TPKS and to identify challenges in its implementation. This study employs normative legal research using statutory and conceptual approaches. The analysis is conducted qualitatively based on relevant legal provisions as well as theories of legal effectiveness, legal protection, and victimology. The findings indicate that normatively, the UU TPKS provides more comprehensive regulations compared to previous laws, particularly regarding victim protection and recovery. However, its implementation still faces challenges, including limited understanding among law enforcement officers, inadequate supporting facilities, and the persistence of victim-blaming culture. Therefore, strengthening institutional capacity, improving inter-agency coordination, and reforming legal culture are necessary to ensure optimal protection for child victims of sexual violence.